Different protocols for piglet creep feeding in the farrowing stage and residual effects in the nursery phase - Zimmer F.* (2022)
© 2022, Academia Brasileira de Ciencias. All rights reserved.This study was aimed at the effects of different Creep-feeding protocols on piglet performance and its residual effects during the nursery phase. Experimental design used was five groups: WC (without creep); DCF (dry creep feeding); WCF (wet creep feeding); LD (additional liquid creep with automatic feed dispenser plus DCF); and LLF (additional liquid creep with linear feeder plus DCF). Ten litters per treatment were selected a total 50 sows and 645 piglets. During the first two weeks of lactation, the LD treatment (2.61 and 4.20 kg) promoted greater body weight (P <0.001) than the DCF (2.55 and 3.93 kg), (WFS) (2.43 and 3.69 kg) and LLF (2.50 and 4.00 kg) treatments, but did not differ from the WC treatment (2.68 and 4.09 kg). At weaning, the WC (5.22 kg), LD (5.32 kg) and LLF (5.27 kg) treatments gave higher body weights (P <0.001) when compared to the DCF (4.97 kg) and WCF (4.69 kg) treatments. We concluded that there was no change in the behavior of the piglets, and the use of dry feed with liquid supplements did not improve weight gain. The different creep feeding systems did not influence the weight and performance of the piglets in the nursery phase.